Evaluasi Kualitas Fisik dan Fitokimia Ransum melalui Kombinasi Daun Lamtoro dan Indigofera - Riswandi, Riswandi; Muhakka, Muhakka; Wijaya, Agus; Imsya, Afnur; Karomah, Cici (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Riswandi R, Muhakka M, Wijaya A, Imsya A, Karomah C. 2022. evaluation of the physical and phytochemical quality of the ration through the combination of leucaena and indigofera leaves. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 254-262. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Tree legume supplementation is a solution to improve the quality of rations in traditional ruminant rearing systems, because they contain high nutrients. The purpose of this study was to evaluate the physical and phytochemical quality of bento grass based rations through the combination of Lamtoro and Indigofera leaves. This research was conducted for 3 months at the Animal Feed Nutrition Laboratory, Faculty of Agriculture, Sriwijaya University. This study used a completely randomized design (CRD) with 4 treatments and 4 replications. The treatments consisted of R0 (70% Bento Rayap Grass + 30% Concentrate), R1 (40% Bento Rayap Grass + 30% Concentrate + 30% Leucaena leaves), R2 (40% Bento Rayap Grass + 30% Concentrate + 30% Indigofera) , R3 ( 40% Bento Rayap Grass + 30% Concentrate + 15% Leucaena leaves + 15% Indigofera). Parameters observed in the physical quality test were specific gravity (SG), pile density (PD), water absorption (WA) and moisture content (MC). Phytochemical analysis consists of tannins and saponins. The results of this study showed that the treatment had a significant effect (P<0.05) on SG, PD, WA, tannin and saponins while the MC had no significant effect (P>0.05). Furthermore, the lowest content of SG (0.47 g/ml) and WA (381.71%) was obtained at R2, the highest PD (0.23 g/cm3) at R1. The highest concentration of tannins (3.16%) and saponins (2.08%) was obtained at R1. The conclusion of this study showed that the combination of 40% Bento Rayap grass + 30% concentrate + 30% Leucaena leaves could improve the physical and phytochemical quality of the ration.